2016
DOI: 10.7151/dmgt.1871
|View full text |Cite
|
Sign up to set email alerts
|

New bounds on the signed total domination number of graphs

Abstract: In this paper, we study the signed total domination number in graphs and present new sharp lower and upper bounds for this parameter. For example by making use of the classic theorem of Turán [8], we present a sharp lower bound on Kr+1-free graphs for r ≥ 2. Applying the concept of total limited packing we bound the signed total domination number of G with δ(G) ≥ 3 from above by n − 2 2ρo(G)+δ−3 2 . Also, we prove that γst(T ) ≤ n − 2(s − s ) for any tree T of order n, with s support vertices and s support ver… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…The signed domination number γ s (G) is the minimum of v∈V (G) f (v) taken over all signed dominating functions f of G, see [18].…”
Section: Additional Invariants On Small Fibonacci Cubes and Hypercubesmentioning
confidence: 99%
“…The signed domination number γ s (G) is the minimum of v∈V (G) f (v) taken over all signed dominating functions f of G, see [18].…”
Section: Additional Invariants On Small Fibonacci Cubes and Hypercubesmentioning
confidence: 99%
“…As an immediate result of Theorem 3.1 we have γ 0 st (G) = −γ st (G), for all cubic graph G. Hosseini Moghaddam et al [3] showed that γ st (G) ≤ 2n/3 is a sharp upper bound for all connected cubic graph G different from the Heawood graph G 14 . Therefore, if G is a connected cubic graph different from G 14 , then γ 0 st (G) ≥ −2n/3 is a sharp lower bound.…”
Section: Regular Graphsmentioning
confidence: 91%
“…Here, we prefer to work with these definitions on these parameters rather than the previous ones. Gallant et al [5] introduced the concept of limited packing in graphs and exhibited some real-world applications of it to network security, market saturation and codes (Also, the authors in [7] presented some results as an application of the concept of the limited packing). A subset…”
Section: Introductionmentioning
confidence: 99%